Pola Pendekatan Orang Tua dalam Menuntun Kegiatan Positif pada Remaja - Samhudi, Samhudi (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2023)
Many teenagers spend time with activities that are not useful. Therefore, parents are required to be able to direct their children to a good path. The purpose of this study was to find out and describe the pattern of parental approaches in guiding positive activities for adolescents in Sumbok Rayeuk Village, North Aceh. Teenagers in the transition phase need full guidance and supervision from their parents, starting from activities at home to outside the home. Parents must always be ready to supervise teenagers in the use of mobile phones and their friendship environment. The research method used is descriptive qualitative. Sources of data in this study were parents in Sumbok Rayeuk Village, North Aceh. Data obtained through interview techniques, documentation, and observation. The results of the study showed that the approach taken by parents in guiding positive activities for Youth in Sumbok Rayeuk Village, Nibong Aceh Utara District was carried out using a communicative approach, reward and punishment patterns and giving exemplary examples to their children. The obstacles faced by parents include the use of mobile phones that do not know a time limit and where adolescents interact with their peers who are beyond the reach of their parents.